The promise of tailoring incentives for healthy behaviors. Issue 1 (7th March 2016) - Kullgren, Jeffrey T.; Williams, Geoffrey C; Resnicow, Kenneth; An, Lawrence C; Rothberg, Amy; Volpp, Kevin G; Heisler, Michele
Abstract : Purpose: – The purpose of this paper is to describe how tailoring financial incentives for healthy behaviors to employees' goals, values, and aspirations might improve the efficacy of incentives. Design/methodology/approach: – The authors integrate insights from self-determination theory (SDT) with principles from behavioral economics in the design of financial incentives by linking how incentives could help meet an employee's life goals, values, or aspirations. Findings: – Tailored financial incentives could be more effective than standard incentives in promoting autonomous motivation necessary to initiate healthy behaviors and sustain them after incentives are removed. Research limitations/implications: – Previous efforts to improve the design of financial incentives have tested different incentive designs that vary the size, schedule, timing, and target of incentives. The strategy for tailoring incentives builds on strong evidence that difficult behavior changes are more successful when integrated with important life goals and values. The authors outline necessary research to examine the effectiveness of this approach among at-risk employees. Practical implications: – Instead of offering simple financial rewards for engaging in healthy behaviors, existing programs could leverage incentives to promote employees' autonomous motivation for sustained health improvements. Social implications: – Effective application of these concepts could lead to programs more effective at improving health, potentially at lower cost. Originality/value: – The approach for the first time integrates key insights from SDT, behavioral economics, and tailoring to turn an extrinsic reward for behavior change into an internalized, self-sustaining motivator for long-term engagement in risk-reducing behaviors.